(untitled) (Economics and region, 2025)
The reform of land relations in Ukraine has one great advantage: it is taking place against the background of many land reforms carried out in the world. Extensive world practice and theoretical knowledge have formed a powerful basis for its implementation. Much has been done in Ukraine on the basis of the traditional understanding of private ownership of land, but there are also subtleties in the understanding of land relations, the understanding of which is directly and indirectly lacking in the modern land reform in our country. At this stage of the study, the article focuses on the methodological approach to understanding land relations based on institutionalism. The author’s methodological concept is that economic processes in the land sector are not subject to classical economic, purely market theories, but to institutional economic theory and have a socio-economic, i.e. institutional, nature. This methodological approach, to a greater extent, complies with the norms of the European Union, in particular with regard to the European innovative policy of green growth.